Cost and quality impacts of treatment setting for type 2 diabetes patients with moderate disease severity: Hospital- vs. GP-based monitoring. Issue 6 (June 2021) - Pulleyblank, Ryan; Laudicella, Mauro; Olsen, Kim Rose
Highlights: Many Danish moderate severity type 2 diabetes patients are treated in a hospital-based outpatient setting Recent policy requires transferring disease management responsibility from hospital to general practice IV analysis suggests reduced healthcare costs are can be expected without increasing demand for emergency hospitalizations Abstract: Objectives: This study investigates cost and quality implications of moving regular monitoring of patients with moderate severity type 2 diabetes (T2D) away from specialized hospital clinics into general practice (GP). Methods: A 2016 cross-section of patients with moderate disease severity T2D were algorithmically identified using Danish administrative databases. 152, 632 GP- and 21, 359 hospital-monitored patients with T2D were identified. Total annual healthcare cost is decomposed into GP, medication, nonhospital-specialist, hospital outpatient and inpatient costs. Hospitalizations are used to proxy for quality of care. Cost and quality impacts of treatment setting are assessed using an instrumental variable (IV) analysis. A wide range of patient confounders are used to reduce selection bias, with the difference in patients' travel-time between nearest specialist outpatient clinic and GP used as an instrument to control for remaining endogeneity of treatment setting. Two-part models are used for zero-inflated outcomes. Results: Average total annual healthcare cost were 14, 056 DKK greater amongst hospital-monitored patients. IV analysis accounting for endogeneity of treatment setting indicates hospital-based monitoring is causally linked to higher total annual healthcare costs. The estimated local average treatment effect of hospital-based monitoring on total annual healthcare costs was higher (117.2%, 95% CI: 23.3%, 211.1%) than GP-based monitoring. No difference of treatment settings' quality based on evidence of hospitalizations was found. Conclusion: For patients with moderate disease severity T2D, IV analysis accounting for treatment setting endogeneity bias identifies an expected efficiency improvement (average cost reduction without reduction of quality) of moving regular disease management from hospital-based setting to the GP setting.